Istitabah model for Malaysia: A preliminary exposition - Wan Mohd Fazrul Azdi Wan Razali; Ahmad Najaa' Mokhtar; Mohd Zaliridzal Zakaria; Kamaluddin Nurdin Marjuni; Mohd Rumaizuddin Musa; Azman Abd Rahman; Mohammmad Fadzil Mat Yaacob (Universiti Sains Islam Malaysia, 2024)
Increasing number of apostasy cases in Malaysia by year have been reported by many authorities.In this sense,istitabah,literally means asking or calling for repentance ,has to be enforced as a national educational and rehabilitation measure.The application of istitabah is considered as obligatory ,and supererogatory by the majority of scholars of Ahl Al-Sunnah Wa Al-Jamaah.This article aims to highlight some findings on the model and approaches of istitabah within the climate of Malaysian religious administration and societal needs.Through the use of qualitative research strategies,it was found that there were only glimpses of istitabah exposition in the classical and modem texts of Islamic scholarship.This has called for present ijtihad to fill in the gaps towards a living practice of istitabah.This article will elucidate a preliminary exposition of M-Istitabah (Malaysia Istitabah),which will become a model for Malaysian Istitabah that applies integrated approach of the principle religion and crisis intervention towarda rehabilitation of apostasy crimes in Malaysia.